Bioethanol Production from Rice Straw Enzymatically Saccharified by Fungal Isolates, Trichoderma viride F94 and Aspergillus terreus F98 - Abo-State, Mervate A.; Ragab, Ahmed M. E.; EL-Gendy, Nour Sh.; Farahat, Laila A.; Madian, Hekmat R. (Scientific Research, 2014)
Egypt faces a high population growth rate nowadays, which demands for an increase in agricultural production efficiency. Consequently, agricultural field residues will increase. Rice straw is one of the main agriculture residues in Egypt. So this study was performed on rice straw as a resource for production of bioethanol. Eight microbial isolates, five yeasts and three fungi were isolated from rice straw. Yeast isolates were selected for their ability to utilize different sugars and cellulose. Chipped and grinded rice straw was subjected to different pretreatment methods physically through steam treatment by autoclaving and different doses of gamma γ irradiation (50 and 70 Mrad). Autoclaved pretreated rice straw was further enzymatically treated throughout solid state fermentation process by different fungal isolates; F68, F94 and F98 producing maximum total reducing sugars of 12.62, 13.58, 17.00 g/L, respectively. Bioethanol production by separate microbial hydrolysis and fermentation (SHF) process of rice straw hydrolysate was performed by the two selected fungal isolates; Trichoderma viride F94 and Aspergillus terreus F98 and two yeast isolates (Y26 and Y39). The two yeast isolates have been identified by 18S, RNA as Candida tropicalis Y26 and Saccharomyces cerevisiae Y39. SHF processes by F94 and Y26 produced 45 gallon/ton rice straw while that of F98 and Y39 produced 50 gallon/ton rice straw.
Keywords: Bioethanol; Rice Straw; Different Pretreatments; Saccharomyces cerevisiae; Candida tropicalis; Separate Hydrolysis and Fermentation (SHF)